FROM DISCOUNTS TO DECISIONS: THE ROLE OF BRAND REPUTATION IN TIKTOK GO'S F&B CONSUMER ECOSYSTEM - Novia Fitri Yanti Saragih; Herning Indriastuti; Heni Rahayu Rahmawati (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to examine the effect of TikTok discount vouchers on consumer purchase decisions in the food and beverage (F&B) sector, with brand reputation as a mediating variable within the social commerce ecosystem. The growing use of TikTok Go as a promotional channel reflects a shift in consumer behavior from passive content exposure to transaction-driven digital engagement. However, the effectiveness of discount strategies in this context is not solely determined by price incentives, but also by perceived brand reputation. This research employs a quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Data were collected through a survey of consumers who have used TikTok discount vouchers for F&B products. The results indicate that TikTok discount vouchers have a positive and significant effect on both brand reputation and purchase decisions. Furthermore, brand reputation significantly influences purchase decisions and acts as a mediating variable in the relationship between discount vouchers and purchase decisions. These findings suggest that the effectiveness of discount strategies in social commerce depends not only on price-based stimuli but also on the ability of brands to maintain a strong reputation. This study contributes to digital marketing literature by highlighting the integration of price promotions and brand perception in shaping consumer behavior.